2014
DOI: 10.5586/asbp.2014.052
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting patterns in the evolution of the Rab GTPase family in Archaeplastida

Abstract: Rab GTPases are a vast group of proteins serving a role of master regulators in membrane trafficking in eukaryotes. Previous studies delineated some 23 Rab and Rab-like paralogs ancestral for eukaryotes and mapped their current phylogenetic distribution, but the analyses relied on a limited sampling of the eukaryotic diversity. Taking advantage of the recent growth of genome and transcriptome resources for phylogenetically diverse plants and algae, we reanalyzed the evolution of the Rab family in eukaryotes wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 62 publications
(103 reference statements)
0
20
0
Order By: Relevance
“…For example, data from carpediemonads, free-living relatives of the parasitic diplomonads, would help answer the question whether the absence of RABL2 from diplomonads correlates with their parasitic lifestyle or whether it reflects an earlier loss that happened already in their free-living ancestor. The critical importance of sampling can further be demonstrated on streptophyte algae, where our previous survey of small GTPases based on a more restricted taxon sampling led to the conclusion that RABL2 (=RTW) was lost before the divergence of Klebsormidium and embryophytes [ 41 ], but our present finding of RABL2 in Coleochaete and Entransia revealed that RABL2 was lost independently from the Klebsormidium and the embryophyte lineages (Fig. 4 ).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…For example, data from carpediemonads, free-living relatives of the parasitic diplomonads, would help answer the question whether the absence of RABL2 from diplomonads correlates with their parasitic lifestyle or whether it reflects an earlier loss that happened already in their free-living ancestor. The critical importance of sampling can further be demonstrated on streptophyte algae, where our previous survey of small GTPases based on a more restricted taxon sampling led to the conclusion that RABL2 (=RTW) was lost before the divergence of Klebsormidium and embryophytes [ 41 ], but our present finding of RABL2 in Coleochaete and Entransia revealed that RABL2 was lost independently from the Klebsormidium and the embryophyte lineages (Fig. 4 ).…”
Section: Discussionmentioning
confidence: 61%
“…A note on nomenclature of RABL2 orthologs must be added here, as it has caused some confusion in the past. Different names have been used to denote RABL2 proteins, including Rab11B ( Trypanosoma brucei RABL2, GenBank accession number AF234189.1), RabX3 ( T. brucei RABL2 [ 39 ]), RabX32 ( Tetrahymena thermophila RABL2 [ 40 ]), Rab_A50 ( Paramecium tetraurelia RABL2 [ 40 ]), and RTW [ 38 , 41 ]. The different nomenclature perhaps confused Lo et al [ 29 ], who appear to have treated sequences denoted RABL2 and RTW as different groups (note also the aberrant topology of their tree presented in their Figure S2, suggesting that the “RTW” and “RABL2” sequences were not properly aligned to each other).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of the ERMES and the Ca 2+ SM in diverse major eukaryotic groups, now including glaucophytes, suggest an ancient origin of these pathways. Likewise, a recent analysis of the archaeplastidian collection of Rab GTPases, which are key regulators of the intracellular membrane traffic, indicates that the GTPase Rab14 is encoded in glaucophyte genomes but not present in the red algal and virdiplant repertoires [100]. The widespread presence of Rab14 in other major eukaryote groups suggests that this protein was part of the Rab GTPase collection of the Archeaplastida common ancestor [100].…”
Section: Phylogenomics Of Cyanophora Paradoxamentioning
confidence: 99%
“…Likewise, a recent analysis of the archaeplastidian collection of Rab GTPases, which are key regulators of the intracellular membrane traffic, indicates that the GTPase Rab14 is encoded in glaucophyte genomes but not present in the red algal and virdiplant repertoires [100]. The widespread presence of Rab14 in other major eukaryote groups suggests that this protein was part of the Rab GTPase collection of the Archeaplastida common ancestor [100]. Further comparative investigations comprising other glaucophyte complete genomes will be important to understand if those glaucophyte genes associated with ERMES, Ca 2+ SM and part of the Rab GTPase family were lost in red algae and viridiplants.…”
Section: Phylogenomics Of Cyanophora Paradoxamentioning
confidence: 99%
“…By using bioinformatics methods, Petrželková and Eliáš [7] demonstrate drastic reduction in the number of Rab GTPase genes in red algae. The absence of Rab5 suggests a significant modification or degradation of the endocytotic pathway in these algae.…”
mentioning
confidence: 99%